Seronegative arthritis. Issue 12 (December 2014) - Kadwani, Hina; Mahmud, Mohammad
The inflammatory arthritides are often divided into those that are 'seropositive' and those that are 'seronegative'. The former test positive with blood tests that look for two proteins: rheumatoid factor; and anti-cyclic citrullinated peptide antibody. However, although seropositivity is part of the diagnostic criteria for rheumatoid arthritis (RA), seronegativity does not exclude the diagnosis, but rather suggests a more benign disease. The term 'seronegative arthritis' has evolved from a term used to describe variants of RA, to the present understanding of a spectrum of 'seronegative spondyloarthritides' (defined as inflammation within the axial skeleton and vertebral column). These are a closely linked group of conditions with common serological, genetic, clinical and radiological features. These include: ankylosing spondylitis; juvenile ankylosing spondylitis; psoriatic arthritis; reactive arthritis; enteropathic arthritis; undifferentiated spondyloarthritis; and seronegative enthesopathic arthritis syndrome. This article will outline the diagnosis and management of seronegative arthritis.